Social capital and local government capacity - Wallis, Joe; Dollery, Brian (2002)
Local authorities vary considerably in their capacity for governance. The dimensions of this capacity can only be developed by drawing on local stocks on social capital. The seminal theories of social capital tend to conceive it as a community resource that is built up through a long tradition of civic engagement. We take issue with the laizzez-faire implications of these theories, highlighting ways in which local governments can positively contribute to social capital formation by opening their `political opportunity structure' and engaging voluntary organisations and community groups in trust-based partnership arrangements. - Reproduced.
Keywords: Local government